Técnicas moleculares para determinar la calidad seminal del bovino sometido a criotolerancia: informe de pasantía de investigación (2022)
The study of the identification of biomarkers that are linked to the seminal quality of the bull, are very important when quantifying proteins and sperm cells that determine the fertility of the bovine male. For this reason, a research internship was carried out in the Tecnho Sperm laboratory with the aim of acquiring training in the techniques to evaluate the seminal quality of bovine males from flow cytometry, western blot and real-time PCR, as conventional techniques. That are carried out in laboratories whose purpose is to determine the biomarkers present in the fertility of cattle. Once the techniques were applied, it was observed that they are very effective and precise to evaluate the viability of the semen from the different alterations that originate when the sperm are subjected to thermal stress during the freezing process. The hypothermic storage of bovine semen allows its cryopreservation without antibiotics, but this process is limited by the high sensitivity of sperm at the time of freezing.